El estrés de docentes universitarios en la Universidad Nacional Hermilio Valdizan - Huánuco - Coletti Escobar, Gabriel (2017)
This research identified the major sources of stress and levels and their potential impact in terms of mental health in university teaching of the National “ Hermilio Valdizán “ University of Huanuco. Psychometric technique, Scale Power Stress University Professors (EFEPU) and Total Health Test (TST ), the method of analysis and synthesis, transseccional descriptive design was used . Was applied in the “ Hermilio Valdizán “ National University - Huanuco , whose population is formed of university faculty UNHEVAL ; was non-probability sampling . Identified sources of stress, affecting, with a level of intensity Severe of UNHEVAL teachers are: 1st teach people who do not value education, 2nd Lack of participation in decision -making  in the Faculty. . Stress levels reflected in university teaching of UNHEVAL show majority are “Troubling” indicating maladjustment in the university context. Potential problems are detected on the mental health of college teachers who can relate to stress, being a hazard or risk of serious mental dysfunction. - It is noted that the Faculty of Veterinary Medicine, Nursing and Sociology, show the highest percentage of teachers with worried level to 100%. - We indicated that the older teachers, 63 to 75 years, show no concern stress levels, by 100 %, while teachers from 37 to 62 years old, and show Troubling” levels The teachers, the male sex, have higher levels of stress, “Troubling “to” Severe” level . - The Graduates, show higher levels of stress, between “Worried” and “Severe”, which together reach 100 %. Teachers with a shorter service between 9-24 years indicate a higher level of “Worried “ stress - . Turns out those teachers with full-time work, show higher levels of stress, with 56 % level “Worried” and “Severe”. Regarding the teaching category, Associates, have a high stress level with 71 % of teachers.